Pengaruh Model Quantum Learning terhadap Hasil Belajar Siswa Mata Pelajaran Bahasa Inggris - Anwar Rohim; Idhotun Nasyi'ah (IBTIDA', 2020)
This study aims to determine the application of the Quantum Learning model, student learning outcomes, and the effect of the application of the Quantum Learning model on student learning outcomes in English subjects grade IV at SDI Ar-Roudloh Miru. This research is a quasi-experimental study using a design in the form of one group pretest and posttest. Data collection techniques using the method of observation and learning outcomes tests. Instrument to measure learning outcomes using pretest and posttest in the form of an objective test. While the data analysis technique uses hypothesis testing. The results showed that, 1) The average observations of the implementation of the implementation of the Quantum Learning model showed very good results with a range of values ​​of 3.7 - 3.9. That is, the application of the Quantum Learning model in English subjects is carried out very well and in accordance with the components of the Quantum Learning model, 2) The assessment of student learning outcomes has increased after the implementation of the Quantum learning model, this assessment can be known from the results of the post-test given to students. Post-test results indicate that a high percentage of learning outcomes are dominated in the range of grades 80-100. That is, students declared complete learning and increased learning outcomes with the application of the Quantum Learning model, 3) The application of the Quantum Learning model in English subjects affected the learning outcomes, as evidenced by testing the hypothesis obtained by r count = 0.869 and r table = .374. In testing the hypothesis the r value is greater than r table, then H0 is rejected and Ha is accepted.